Best Answer

What I would do is change the problem up. Instead of b-9b I would make it -(9b-b). It is still the same problem; you will multiply the number inside the parenthesis be -1. So start with 9b-b. That would equal 8b. So it would change from -(9b-b) to -(8b) so you multiply 8b by negative 1 (-1) to get the answer -8b. -8b is your answer. So b - 9b = -8b

🙏

🤨

😮

Study guides

Q: What is b - 9b simplified?

Write your answer...

Submit

Related questions

If you mean: 7b+b+b then it is 9b simplified

The simplified expression is -9a -9b.

When simplified it is: 2a+8b+4

9b + 6 - 8 = -36 9b = -38 b = 4.2222222(repeating)

It is not an equation but an algebraic expression that can be simplified to: 12b-5a

If you mean: (3b+7)^2 then it is 9b^2+42b+49

The LCM of 9b and 12 b is 36b. LCM is Least Common Multiple.

8b^2 -9b +1 8b^2 -8b -b +1 8b(b-1) - 1(b-1) (8b-1)(b-1)

b= 10

10b

It is: B+2b when simplified assuming B and b have different values

Gh

eek

9b-13b= -4b -4b = 40 Divide both sides by -4 b = -10

It is: 2a+5a = 7a when simplified

bxb

(2b - 5)(b + 7)

All the terms in b add to 11, so 11b = 132 making b = 12

Two ratios, a/b and c/d have the same value is a*d = b*c. A ratio, a/b, is said to be simplified if a and b are co-prime.

It is: b -8 when simplified

b/2

If it is a fraction 128/144 can b simplified to 8/9.

It is: 60+b simplified

Since 3b is a factor of 9b, it is automatically the GCF.

3A + 9B = 3(A + 3B)